PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CONNECTING, ORGANIZING, REFLECTING, AND EXTENDING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII MTSN 5 PADANG - Ikhtiara, Putri Zuliarti; Jamaan, Elita Zusti (Jurnal Edukasi dan Penelitian Matematika, 2024)
Mathematical communication ability are one of the sought-after elements in the implementation of mathematics learning and must be mastered by students. Based on observation, the mathematical communication ability of eight-grade students of MTsN 5 Padang is weak. One effort to address this issue is to apply the Connecting, Organizing, Reflecting, and Extending cooperative learning model. This research aimed to analyze linked to the existence of better mathematical communication ability of students who, during their studies, apply the CORE type cooperative learning model than those who study using direct learning and describe how students' mathematical communication develop during the implementation of the model. The research conducted was quasi-experimental and descriptive with posttest-only nonequivalent control groups design. The population consists of eight-grade students MTsN 5 Padang in the 2023/2024, the experimental group being class VIII.11 and the control group being class VIII.10. The quiz analysis results show that there are two models of skill development, namely constant increase and fluctuation. Final test analysis show that the mathematical communication ability of students who study using the CORE-type cooperative learning model are better than those who study using the direct learning model in class VIII MTsN 5 Padang.Keywords– Mathematical communication ability, Cooperative learning model, CORE, Direct instruction model